Elasticity module and hardness of niobium and tantalum anode oxide films - Dub, S.N.; Starikov, V.V. (Functional Materials, 2007)
The elasticity modulus and hardness of oxide films obtained by anodic oxidation of niobium and tantalum have been studied. Relation of these characteristics with surface oxide thickness has been considered. It is established that the amorphous oxide coatings of small thickness show an anomalous high elasticity and are capable to withstand considerable deformations without the oxide film failure. This property is lost when the oxide film thickness increases. For the first time the elasticity module and hardness values for anodic niobium and tantalum oxide films of various thickness have been obtained.